A new genus and two new species of hymenosomatid crabs (Crustacea:Brachyura: Hymenosomatidae) from the southwestern Atlantic and eastern Australia - Tavares, Marcos; Santana, William (Zootaxa, 2015)
A new genus, Teramnonotus n. gen., is erected for Elamena gordonae Monod, 1956. The new genus includes two new species, T. johnlucasi n. gen., n. sp. and T. monodi n. gen., n. sp., described herein from eastern Australia (Queensland) and the southwestern Atlantic (Brazil), respectively. Teramnonotus n. gen. superficially resembles Elamena H. Milne Edwards, 1837, and Trigonoplax H. Milne Edwards, 1853, of which it can be easily distinguished by a combination of characters: eyes and ocular peduncle, rostrum, carapace, thoracic sternite 8 and thoracic pleurite 8, and the inhalant water openings. The validity of the obscure species Elamena mexicana H. Milne Edwards, 1853, is not supported and it is synonymised with Halicarcinus planatus (Fabricius, 1775).